Hepatoprotective Effect of Alcoholic Extract of Ficus carica Leaves ‎Against ‎‎Cypermethrin-Induced Liver Toxicity in Male Albino Rats - Ismael Abbasa, Mina; JM Jawad, Zainab (The Iraqi Journal of Veterinary Medicine, 2023)
Cypermethrin (CYP), a synthetic pyrethroid, is recognized for its insecticidal properties but ‎poses potential risks of hepatotoxicity. In traditional medicine, Ficus (F.) carica (common ‎fig) leaves have historically been used for various therapeutic applications. This study ‎aimed to evaluate the hepatoprotective effect of the methanolic extract of F. carica‎‎ leaves ‎against CYP-induced liver damage in adult male albino rats (Rattus norvegicus). The ‎animals (n=30), 8-12 weeks old ‎and weighing 200-250 g‎, were randomly divided into five ‎experimental groups (n=6) and treated as follows: the negative control group received ‎distilled water; the CYP-Only group was exposed to 4.74 mg/kg BW for 45 days; the ‎CYP+post-treatment group received the same CYP dosage followed by F. carica‎‎ methanolic ‎leaf extract at 500 mg/kg BW orally for two weeks; the pre-treatment+CYP group received ‎ ‎F. carica‎‎ methanolic leaf extract at 500 mg/kg BW orally for two weeks followed by CYP ‎exposure for 45 days; and the F. carica‎‎ extract-Only group was administered the methanolic ‎leaf extract at 500 mg/kg BW orally for two weeks. At the end of the experiment, serum and ‎liver samples were analyzed for biochemical and histopathological changes. CYP-Only ‎exposed group showed significantly increased serum alanine aminotransferase (ALT) and ‎alkaline phosphatase (ALP) and caspase-3 levels (P<0.05). Histopathological examination ‎in group exposed CYP only revealed liver damages as evidenced by central vein congestion, ‎scattered perivascular mononuclear cell infiltration, prominence of ‎Kupffer cells, nuclear ‎pyknosis, and severe hepatocytic necrosis. Treatment with F. carica‎‎ leaf extract, either ‎before or after CYP exposure, as well as solely with F. carica‎‎ leaf ‎‎extract, ameliorated both ‎the biochemical and histological indices of liver ‎damage. The findings suggest that the ‎methanolic extract of F. carica‎‎ leaves provides promising hepatoprotective effects against ‎CYP-induced liver damage in albino rats, likely via its antioxidative properties‎‎.